2005
DOI: 10.1139/t05-058
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic shear response of fine-grained mine tailings

Abstract: The mechanical response of three different types of fine-grained mine tailings is examined using data from constant-volume cyclic direct simple shear (DSS) tests. Under cyclic DSS loading, fine-grained tailings typically exhibit a cumulative decrease in effective stress along with progressive degradation of shear stiffness. The observed shear strain development due to cyclic mobility is similar in form to that of the previously observed cyclic shear response for natural silts. The cyclic resistance ratio (CRR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(43 citation statements)
references
References 26 publications
7
28
2
2
Order By: Relevance
“…8, it can be seen that the void ratio versus normalized cyclic resistance ratio data obtained by Sanin and Wijewickreme (2006); Wijewickreme et al (2005) and Ishihara et al (1980) fall within the established boundaries in the present study. The CRR results from Cyclic Direct Simple Shear (DSS) tests obtained from other researchers were transformed into an equivalent Cyclic Triaxial values using Eq.…”
Section: Resistance Of Tailings and Natural Soil To Cyclic Loadingsupporting
confidence: 85%
See 2 more Smart Citations
“…8, it can be seen that the void ratio versus normalized cyclic resistance ratio data obtained by Sanin and Wijewickreme (2006); Wijewickreme et al (2005) and Ishihara et al (1980) fall within the established boundaries in the present study. The CRR results from Cyclic Direct Simple Shear (DSS) tests obtained from other researchers were transformed into an equivalent Cyclic Triaxial values using Eq.…”
Section: Resistance Of Tailings and Natural Soil To Cyclic Loadingsupporting
confidence: 85%
“…Sitharam et al (2004) discussed the variation of normalized residual strength (i.e., with effective confining pressure) of soils with void ratio. Wijewickreme et al (2005) observed the variation of post cyclic maximum shear strength ratio with void ratio for two mine tailings. Peters and Verdugo (2003) showed the susceptibility of mine tailings to liquefaction and the need to further understand the response of tailings to cyclic loading.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to Wijewickreme et al (2005), the preponderance of laboratory studies on mine tailings has not been performed using cyclic simple shear equipment and the studied stress paths therefore do not simulate the cyclic rotation of principal stresses that takes place during earthquake loading. Previous studies (Arthur et al, 1980;Wijewickreme & Vaid, 1993) showed that most soils experience deformations due to changes in the magnitudes of principal stresses and also to changes in their directions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Arthur et al, 1980;Wijewickreme & Vaid, 1993) showed that most soils experience deformations due to changes in the magnitudes of principal stresses and also to changes in their directions. The variation of shear stresses under cyclic conditions along with changes in the direction of principal stresses is achieved during cyclic direct simple shear tests (Wijewickreme et al, 2005). Vaid & Finn (1979) considered the direct simple shear test as the most appropriate for the simulation of earthquake loading conditions.…”
Section: Introductionmentioning
confidence: 99%